2021
DOI: 10.3390/s21072428
|View full text |Cite
|
Sign up to set email alerts
|

User Experience of the Mobile Terminal Customization System: The Influence of Interface Design and Educational Background on Personalized Customization

Abstract: The study verified the role that different interface designs and users’ educational backgrounds play in the task performance and subjective evaluation of mobile terminal customization system. Interface type (based on scroll, alternative, and attribute) and user group (college students and industrial workers) were employed as the variables. A total of 72 users were included in the study, and an analysis of 3 × 2 between-participants design indicated that (1) Different interface designs of customization systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Therefore, we have reason to believe that when the subjects are not college students but the elderly, the results of the study are likely to change. Yi et al [49] reported that educational level affected the user's preference for interface layout, and the user group with a higher educational level (such as college students) preferred an interface with rich operational gestures, which was contrary to our finding. In our study, compared to the waterfall-type layout, juxtaposition-type layout adds the gesture of sliding left and right but it does not receive preference because of this new gesture.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, we have reason to believe that when the subjects are not college students but the elderly, the results of the study are likely to change. Yi et al [49] reported that educational level affected the user's preference for interface layout, and the user group with a higher educational level (such as college students) preferred an interface with rich operational gestures, which was contrary to our finding. In our study, compared to the waterfall-type layout, juxtaposition-type layout adds the gesture of sliding left and right but it does not receive preference because of this new gesture.…”
Section: Discussioncontrasting
confidence: 99%
“…Interface layout was another independent variable. As we have introduced in related work, interface layout can affect people's cognitive process, which has been confirmed by multiple research fields [47,49,51]. Considering that all of our subjects were Chinese, the interface layout should conform to the user's habits and experience from the perspective of cognitive psychology [51], so this study analyzed 26 common interface layouts of digital education Apps in China rather than in overseas markets as the source of inspiration for layout design.…”
Section: Interface Prototype Design and Manipulation Checkmentioning
confidence: 85%
See 2 more Smart Citations
“…Numerous scholars have explored HRIs from different perspectives. Yi et al [5] verified the role played by different interface designs and users' educational backgrounds on task performance and subjective evaluations of mobile terminal customization systems. Reddy et al [6] investigated whether, for older adults, redundancy in the interface is advantageous over text or symbol-based interfaces during early or intermittent device use.…”
Section: Introductionmentioning
confidence: 99%